Case Report: Giant cell-rich osteosarcoma of the cervical spine in the pediatric age. A rare entity to consider - Egea-Gámez, Rosa M.; Galán-Olleros, María; González-Menocal, Alfonso; González-Díaz, Rafael (Frontiers in Surgery, 2022)
Background: Although osteosarcoma is the most common primary malignant bone tumor in children, its location in the axial skeleton is rare, particularly at the cervical spine. Early diagnosis, together with multidisciplinary management, improves survival rates. Safe resection and stable reconstruction are complicated by the particular anatomy of the cervical spine, which raises the risks. Case Presentation: A 12-year-old male patient presented with cervical pain for several months and a recent weight loss of 3 kg. The complementary workup revealed a large destructive bone lesion in C7 with vertebral body collapse, subluxation, partial involvement of C6 and T1, large associated anteroposterior soft tissue components, and spinal canal narrowing. A biopsy suggested giant cell-rich osteosarcoma (GCRO). After 10 cycles of neoadjuvant chemotherapy, surgical resection was performed through a double approach: anterior, for tumoral mass resection from C6-7 vertebral bodies and reconstruction placing a mesh cage filled with iliac crest allograft plus anterior plate fixation; and posterior, for C7 complete and C6 partial posterior arch resection, thus completing a total piecemeal spondylectomy preserving the dura intact, added to a C5-T3 posterior fusion with screws and transitional rods. Postoperative chemo and radiotherapy were administered. Clinical and radiological follow-up showed disease-free survival and no neurological involvement at 3 years. Conclusion: An extensive review of the literature did not find any published cases of GCRO of the cervical spine in pediatric patients. This can be explained by the combination of three peculiar conditions: its location at the cervical spine region, the young age, and the GCRO variant.